Prinsip Keadilan dalam Pemberian Kompensasi pada Karyawan Home Konveksi - Ilmia Rofi; Hanif Noer Kholis; Rudy Haryanto (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study aims to explore the principle of justice in compensating employees of home convection. This research was conducted at home convection in Paterongan village. The type of research in this study uses descriptive qualitative methods based on the results of observations and interviews using Sugiyono's analysis techniques. The results showed that home convection in compensating employees there are two forms of compensation, namely direct compensation and indirect compensation. Direct compensation is given in the form of salaries and bonuses. While indirect compensation in the form of allowances including lunch allowances and holiday allowances. The basis of the principle of fairness in compensation is explained in Mondy's theory, the Qur'an and Hadith, and raises Dessler's opinion. The provision of home convection compensation in Paterongan village applies the principle of justice as evidenced by the payment of wages in accordance with the agreement and employee responsibilities, not delaying payment and providing allowances and bonuses with the aim of improving employee performance and as a form of responsibility of business owners to employee rights.